Long-term Postoperative Outcomes of Pediatric Cataract Extraction with IOL Implantation in a Tertiary Eye Care Centre at Karachi: Postoperative Outcomes of Pediatric Cataract Extraction with IOL Implantation - Uddin, Muhammad Moeez; Shah, Shahid Hussain; Rameez, Faiza; Khan, Muhammad Muslim; Azam, Muhammad; Shaikh, Shoaib Ahmed (Pakistan Journal of Health Sciences, 2025)
Cataracts in the pediatric age group present with challenges distinct from the adult age group. Objectives: To determine the long-term postoperative outcomes of pediatric cataract extraction with IOL implantation at a tertiary eye care center in Karachi. Methods: This retrospective cross-sectional study was carried out at Al-Ibrahim Eye Hospital for six months after ethical approval. Medical records of pediatric children below 10 years that had undergone cataract surgery along with implantation of IOL at the hospital in-between January 2020 to December 2024 were selected. Children having abnormalities, such as condition limiting eye’s visual potential like retinal disorders, retinal detachment, glaucoma, persistent fetal vasculature, abnormalities of the cornea, diseases of optic nerve, uveitis (either active or signs suggesting history of uveitis), or a history of cryotherapy for retinopathy due to prematurity, or treatment with laser, children with complications of surgery, placement of IOL in sulcus or children that failed to follow-up were all excluded. SPSS version 23.0 was used for data analysis. Results: A total of 140 eyes from pediatric patients were studied, with 56.43% male and 43.57% female. Bilateral cataracts were more common (72.86%). The mean age at surgery was 74.77 ± 29.94 months, with a follow-up of 5.22 ± 3.82 months. Postoperative refractive biometry significantly improved from +24.50 ± 4.50 D to +18.50 ± 2.50 D (p<0.001), showing a mean reduction of -6.00 ± 2.00 D. Conclusions: In long-term post-operative outcomes of pediatric cataract extraction with IOL implantation, surgery was generally well-tolerated with positive outcomes and minimal side effects.